คุณภาพการสอบบัญชีและการจัดการกำไร: Audit Quality and Earnings Management - Kaewprapa, Kanok-on; Khailaihong, Ratiya; Khanwang, Orapan (Asian Health, Science and Technology Reports, 2014)
การสอบบัญชีถือเป็นกลไกสาคัญในการลดระดับการจัดการกาไร เพราะการสอบบัญชีเป็นกระบวนการในการตรวจสอบ และแสดงความเห็นต่องบการเงินว่ามีความถูกต้องตามควรและปราศจากการแสดงข้อมูลที่ขัดต่อข้อเท็จจริงอันเป็นสาระสาคัญ แต่หลาย ๆ ฝ่ายมักเชื่อว่าคุณภาพในการสอบบัญชีของสานักงานสอบขนาดใหญ่ (Big-4) ดีกว่าสานักงานสอบบัญชีโดยทั่วไป (Non-Big 4) ดังนั้น วัตถุประสงค์ของงานวิจัยนี้ คือ เพื่อศึกษาความแตกต่างของคุณภาพการสอบบัญชีของกลุ่ม Big 4 และกลุ่ม Non-Big 4 ที่มีผลต่อระดับการจัดการกาไรของบริษัทจดทะเบียนในตลาดหลักทรัพย์ในกลุ่มสินค้าอุตสาหกรรม จานวน 77 บริษัท ในช่วงปี พ.ศ. 2554-2555 โดยใช้ตัวแบบจาลองของ Jones (1991) ทดสอบรายการพึงรับพึงจ่ายตามดุลยพินิจของฝ่ายบริหาร (Discretionary Accruals : DCA) เป็นตัวแทนของระดับการจัดการกาไรและใช้ขนาดของสานักงานสอบบัญชี (Big 4 or Non-Big 4) เป็นตัวแทนของคุณภาพการสอบบัญชี ผลการวิจัยพบว่า กลุ่มบริษัทจดทะเบียนที่ได้รับการสอบบัญชีโดยกลุ่ม Big-4 มีระดับค่าเฉลี่ยของ DCA น้อยกว่ากลุ่มบริษัทจดทะเบียนที่ได้รับการสอบบัญชีโดยกลุ่ม Non-Big 4 แต่ไม่พบความแตกต่างอย่างมีนัยสาคัญทางสถิติ ณ ระดับ0.05 ดังนั้น การศึกษาครั้งนี้ไม่พบหลักฐานที่ยืนยันได้ว่าคุณภาพของการสอบบัญชีโดยกลุ่ม Big-4 จะลดระดับการจัดการการกาไรได้มากกว่ากลุ่ม Non-Big 4 อย่างมีนัยสาคัญทางสถิติ An audit is a key mechanism reducing the levels of earnings management because this is an audit process and expressing an opinion by auditors that financial statements are presented fairly and free from material misstatements. However, many parties often believe that an audit quality of big audit firm size (Big-4) is better than ones (non-Big 4). The objective of this research is to study the difference of audit quality between Big-4 and non-Big 4 affecting the levels of earnings management. 77 listed firms in the industrial goods’ industry group were selected as the sample for collecting and analyzing the financial data between the period 2011 and 2012. Jones Model (1991) was applied for testing discretionary accruals as a proxy of earnings management and audit firm size (Big 4 or Non-Big 4) was used as a proxy of audit quality. The result showed that the listed firms audited by Big 4 have the lower levels of discretionary accruals than those audited by Non-Big 4, but not significantly (p<0.05). Therefore, the findings could not empirically confirm the audit quality of Big 4 better than Non-Big 4 for reducing the levels of earnings management.